Resilience in Industry 4.0 Digital Infraestructures and Platforms - Daniel de Sousa Ribeiro (2021)
We live in a world where companies are shifting toward the industry 4.0 paradigm. One of the pillars of Industry 4.0 (i4.0) is the digitalization of physical assets and manufacturing and business processes towards the Cyber-Physical Production Systems concept (CPPSs). CPPSs are distinguished by highly versatile production processes capable of adapting to the current market conditions and manufacturing a wide range of small-batch items. As a result of modern applications of cyber-physical production systems, modified frameworks, and more complex IT infrastructures, new types of disruption events may occur. In the case of process disruption, actions must be taken in a short time to minimize the impact on production systems. Hence, companies that adhere to i4.0 enabling technologies must protect themselves against these unexpected problems by introducing disruption management solutions. This dissertation introduces a simulation-based methodology capable of evaluating the impacts of disruption events and finding suitable response actions to increase resilience in Cyber-Physical Production Systems processes.